PENGARUH FINANCIAL DISTRESS, AUDIT TENURE, UKURAN PERUSAHAAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN TRASPORTASI DAN LOGISTIK - Khuzaeni Khuzaeni; Satiman Satiman (UNIVERSITAS DHARMAWANGSA, 2026)
This study was conducted to analyze the influence of financial distress, audit tenure, and company size on the issuance of a going-concern audit opinion in transportation and logistics companies. The study population was 37 transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The methodology used was logistic regression. Purposive sampling was used to select 19 companies, resulting in a five-year sample period from 2019 to 2023, resulting in 95 samples. Data were taken from the audited consolidated financial statements published by each company. Hypothesis testing was conducted using Eviews Series 12. The results showed that financial distress, audit tenure, and company size simultaneously influenced the issuance of a going-concern audit opinion. Financial distress partially influenced the issuance of a going-concern audit opinion, while audit tenure and company size did not.